A CASE SERIES OF STRONGYLOIDES STERCORALIS INFESTATION AMONG PATIENTS ATTENDING TERTIARY CARE CENTRE AT RURAL KANCHEEPURAM DISTRICT - DIVYA .G,; NITHYA.G, (International Journal of Pharma and Bio Sciences, 2016)
Strongyloides stercoralis, a neglected nematode is widely prevalent all over the world. Risk factors of the infestations are HIV, immunosuppressive therapy, diabetes, malignancy. Chronic cases will develop hyperinfection or disseminated strongyloidiasis, resulting in high mortality rate upto 87%. One year data of stool microscopic investigations was analyzed for Strongyloides stercoralis infestation. Total of 1550 stool samples were analyzed. Out of which 285 (18.3%) samples were positive for ova/cyst or larvae. 11 stool samples showed positive for the presence of Strongyloides stercoralis larvae. Most of the cases presented with gastrointestinal symptoms, anaemia, Diabetes mellitus, hypertension, one on corticosteroid and others did not have any high risk symptoms. All are HIV negative. Co infection of helminths was seen in one case. Hence it is very important to suspect even immunocompetent patients with gastrointestinal symptoms in terms of Strongyloides stercoralis infestation. This will be helpful in timely diagnosis, treatment and recovery of the patients.